Blue is for nightmares - Stolarz, Laurie Faria,frey50 (Woodbury, Minn. : Llewellyn, 2003)
Sixteen-year-old hereditary witch Stacey Brown has nightmares of her roommate being murdered and hopes that her magic will be enough to protect Drea--unlike the last person whose death Stacey dreamed.
Keywords: Witchcraft; Magic; Stalking; Schools; Extrasensory perception; Witchcraft; Magic; Stalking; Schools; Extrasensory perception; Occult fiction; Children's stories